2017
DOI: 10.20944/preprints201711.0014.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Helical Charge Simulation based 3-D Method for Calculating AC Stranded Conductor’s Corona Loss in the Corona cage

Abstract: Corona loss generated from conductors is one of the important design factors on ac 21

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…Furthermore, unlike homogeneous QDs, gradient alloyed QDs with funnel-shaped bands can simultaneously possess both a narrow band gap for broadening the light absorption range and a negative (positive) conduction band (valence band) edge for accelerating efficient photogenerated electron (hole) transfer from the QDs to the substrate to boost the reduction (oxidation) performances. 24 According to a previous report, 25 this quasi-type II energy-band structure of gradient alloyed QDs can significantly facilitate photogenerated electron−hole separation, and their superior performances related to hydrogen production, 26 pollutant degradation, 27 and photodetectors 28 have been confirmed in our previous studies. Therefore, it is worthwhile to assess the application of gradient alloyed QDs in photocatalytic lignin valorization.…”
Section: Introductionsupporting
confidence: 73%
“…Furthermore, unlike homogeneous QDs, gradient alloyed QDs with funnel-shaped bands can simultaneously possess both a narrow band gap for broadening the light absorption range and a negative (positive) conduction band (valence band) edge for accelerating efficient photogenerated electron (hole) transfer from the QDs to the substrate to boost the reduction (oxidation) performances. 24 According to a previous report, 25 this quasi-type II energy-band structure of gradient alloyed QDs can significantly facilitate photogenerated electron−hole separation, and their superior performances related to hydrogen production, 26 pollutant degradation, 27 and photodetectors 28 have been confirmed in our previous studies. Therefore, it is worthwhile to assess the application of gradient alloyed QDs in photocatalytic lignin valorization.…”
Section: Introductionsupporting
confidence: 73%
“…A research [10] has shown that trait anxiety and positive in uence were important predictors of career decision-making self-e cacy. In the eld of nursing, most domestic researchers mainly focus on the curren situation and in uencing factors of job-seeking e cacy, and few studies focus on job -seeking e cacy and employment anxiety [9]. Furthermore, social support has a positive effect on coping with stress and thus, safeguards mental health [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finding a job is generally a stressful and challenging process, associated with discouragement, frustration and anxiety. Employment anxiety can lead to ineffective learning, performance, and unhealth outcomes [7][8].In addition, previous studies showed that job self-e cacy was a predictor of employment anxiety.among graduates [9][10]. Also, higher levels of job-seeking self-e cacy have been found to be positively associated with lower anxiety [11]However, there has been no study on the relationship between employment anxiety and job seeking e cacy among student nurse interns.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence and intensity of corona discharges, and hence their losses, is affected by the following factors: The electric field gradient on the conductor surface [16,17], the conductor surface condition [6,18], weather conditions [19][20][21], the relative air density [22,23], the effect of water on the conductor surface [20,22], the average operating voltage of the line [19,24,25], the size of phase conductors [18,26], bundled conductor lines [5,12,16,17], the existence or not of shield conductors [27], the sag value of the phase and shield conductors [28], the line unbalance and the type of structure.…”
Section: Introductionmentioning
confidence: 99%
“…There are other methods for the calculation of corona losses in transmission lines, such as Ryan and Henline [36], Carroll and Cozzens [18,37,38] and others, using different approaches. Peterson, in 1933, in a AIEEE discussion, proposed a formula for fair weather corona loss which has been become a classic part of the literature on the subject [28,[39][40][41]. However, these methods have two main disadvantages, the first one is that they perform the calculations in good weather conditions and the second is that they assume that the transmission lines are symmetrically transposed.…”
Section: Introductionmentioning
confidence: 99%